Water Quality Assessment at Liubena Spring, Fatunisuan Village Based on Physical, Chemical and Biological Parameters - Ni Made Dewi Anjelina; Sefrinus Maria Dolfi Kolo; Made Santiari; Hernur Yoga Priyambodo (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: The water from the Liubena spring has been used by the community as drinking water, but its quality has never been tested. Water quality can affect health and the economy. Methodology: This research is quantitative. Water sampling was conducted in the morning at a single sampling point. Water samples for laboratory testing were collected, stored in PP bottles and dark glass bottle, and then placed in a cool box. The parameters measured in the field were pH, temperature, and DO. pH and temperature were measured according to the Standar Nasional Indonesia (SNI) method, while DO was measured according to the instrument's instructions. Other parameters are measured using methods used in testing laboratories. The test results were analyzed descriptively, namely, by comparing them with the water quality standards for Hygiene and Sanitation purposes, as set out in the Regulation of the Minister of Health of the Republic of Indonesia Number 32 of 2017. Findings: The parameter values for TDS, water temperature, hardness (CaCO3), and pH are, respectively, 315 mg/L, 19°C, 334 mg/L, and 7, all of which still meet the quality standards. The parameter values of DO, BOD, COD, TSS, and Iron (Dissolved Metal) are respectively 3 mg/L, 2,90 mg/, 3,51 mg/L, 1,5 mg/L, and 0,271 mg/L, which cannot be compared with quality standards because no values are available. The total coliform value (20 quantity/100 mL) cannot be compared with the quality standard because the units differ. E. coli and fecal coliform testing are necessary to determine whether the water is contaminated and and to trace the contamination source. TDS, temperature, hardness, and pH parameters still meet quality standards; meanwhile, DO, BOD, COD, TSS, Iron (Dissolved Metal), and total coliform parameters cannot be compared with quality standards.  Contribution: This research data can serve as baseline data for developing sustainable water management strategies